Perlindungan Hukum bagi Kreditur dalam Penarikan Paksa Objek Jaminan Fidusia di PT. Astra Credit Companies Kota Padang - Fajri Hasrul; Busyra Azheri; Muhammad Hasbi (LPPM Universitas Ekasakti Padang, 2023)
This study aims to identify and analyze forced withdrawals carried out by PT. ACC Padang Branch and the problems faced by the company in the process of forcibly withdrawing collateral objects. This research was conducted by juridical-empirical research. The data source for this research is primary data from key informants at PT. ACC Padang Branch and secondary data derived from legal reference sources. The results of the study at the ACC Padang Branch found that the forced withdrawals based on the two cases analyzed had been carried out according to the requirements stated in the UUJF and the Constitutional Court Decision Number 18/PUU-XVII/2019. Based on these two cases the debtor has defaulted and has no good faith to settle his obligations. This study found that the debtor had violated Article 23 UUJF, by transferring the collateral object without the creditor's approval. By UUJF, in this case, the creditor can not only make withdrawals but the debtor can also be punished according to Article 36 UUJF.